2013
DOI: 10.1111/jmg.12039
|View full text |Cite
|
Sign up to set email alerts
|

Origins of yttrium and rare earth element distributions in metamorphic garnet

Abstract: Highly variable distributions of yttrium and rare earth elements (Y+REEs) are documented in pelitic garnet from the Picuris Mountains, New Mexico, and from Passo del Sole, Switzerland, and in mafic garnet from the Franciscan Complex, California. The wide variety of these Y+REE zoning patterns, and those described previously in other occurrences, imply diverse origins linked to differing degrees of mobility of these elements through the intergranular medium during garnet growth. In the Picuris Mountains, large,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 34 publications
3
82
1
Order By: Relevance
“…Nonetheless, original trace element growth zoning is believed to be substantially modified under granulite facies conditions (e.g. Carlson, 2012;Kelly et al, 2011;Moore et al, 2013;Otamendi et al, 2002;Skora et al, 2006). For example, Kelly et al (2011) report substantial flattening of originally steep Y + REE concentration profiles in garnet from the Taiuyak Gneiss, Labrador, and attribute this to protracted residence (∼65 Myr) under very high-grade conditions (∼850 • C, 6-9 kbar).…”
Section: Cooling Historymentioning
confidence: 93%
See 1 more Smart Citation
“…Nonetheless, original trace element growth zoning is believed to be substantially modified under granulite facies conditions (e.g. Carlson, 2012;Kelly et al, 2011;Moore et al, 2013;Otamendi et al, 2002;Skora et al, 2006). For example, Kelly et al (2011) report substantial flattening of originally steep Y + REE concentration profiles in garnet from the Taiuyak Gneiss, Labrador, and attribute this to protracted residence (∼65 Myr) under very high-grade conditions (∼850 • C, 6-9 kbar).…”
Section: Cooling Historymentioning
confidence: 93%
“…Compositional mapping of yttrium in peak metamorphic garnet shows the preservation of prograde-style growth zonation (Carlson, 2012;Moore et al, 2013;Pyle and Spear, 1999) with a moderately high-Y core and a relatively low-Y rim (Figs. 6 and 7).…”
Section: Duration Of High-temperature Conditionsmentioning
confidence: 96%
“…The data and recent synthesis of Moore et al (2013) revealed that Y+REEs may sometimes exhibit smooth zoning with pronounced central peaks, demonstrating equilibration over long length scales with an unchanging matrix assemblage (e.g., Otamendi et al 2002), or they may exhibit various annular maxima, demonstrating equilibration, over similarly long length scales, with changing accessory-or major-phase assemblages that are modulated by reactions occurring within the matrix (e.g., Pyle and Spear 1999;Konrad-Schmolke et al 2008). But Moore et al (2013) stressed that in other circumstances, these elements may express disequilibrium during garnet growth, in the form of overprint zoning (Martin 2009), diffusion-limited uptake (e.g., Skora et al 2006), or control by external fluids that did not equilibrate with the matrix mineral assemblage (Moore et al 2013). In all cases, the principal factor that determines the length scale for equilibration is the rate of intergranular transport.…”
Section: Evidence From Mineral Zoningmentioning
confidence: 96%
“…The high metamorphic temperature (~600 o C) and the presence of abundant hydrous minerals, i.e., amphibole, epidote, paragonite and talc, in the matrix do not support diffusion-dominated garnet growth (Moore et al, 2013). Thus, the deduced P-T paths of the growth of the garnet outer rim and matrix amphibole are credible.…”
Section: Pseudosection and P-t Estimatesmentioning
confidence: 96%